Societal Cost-Benefit Analysis of Small-Scale JUJU DHAU Dairy in Bhaktapur Municipality - Adhikari, Padma Kumar; Lamichhane, Kul Prasad; Gajurel, Ram Prasad (Economic Review of Nepal, 2024)
This study, entitled Societal Cost-Benefit Analysis of Small-Scale JUJU DHAU Dairy in Bhaktapur Municipality, was designed to evaluate the economic viability and social impact of JUJU DHAU production on the Newar community, using data from 50 producers collected between December 2022 and January 2023 under funding provided by UGC Nepal (SRDIG-78/79- H&S-02) program and applying cost-benefit analysis to assess costs, revenues, and effectiveness in a societal context. The findings of this study revealed that producers spent Rs. 31280, earned an average monthly income of Rs. 53,600, and saved Rs. 22,320. The benefit-to-cost ratio (1.295) and the internal rate of return (2.72) demonstrated the strong economic potential of JUJU DHAU trades. This study recommends supporting these local industries, improving market access, reducing production costs, and expanding JUJU DHAU production beyond Bhaktapur by using modern marketing strategies. The implications thereof are that these initiatives could create a niche in the JUJU DHAU market and boost economic opportunities by preserving cultural heritage on the one hand and striking a proper balance between traditional practices and socioeconomic sustainability in a globalized context on the other.